Sussex by the sea: A descriptive analysis of dialect variation in the South East of England based on English Dialect App data. Issue 3 (September 2020) - Jansen, Sandra; Robinson, Justyna A.; Cahill, Lynne; Leemann, Adrian; Blaxter, Tamsin; Britain, David
Abstract : Dialects in the South East of England are very often perceived as one homogenous mass, without much regional variation. Rosewarne introduced the notion of Estuary English and defined it as 'variety of modified regional speech [ . . . ] a mixture of non-regional and local south-eastern English pronunciation and intonation' (Rosewarne, 1984). However, studies such as Przedlacka (2001) and Torgersen & Kerswill (2004) have shown that, at least on the phonetic level, distinct varieties exist. Nevertheless, very few studies have investigated language use in the South East and even fewer in the county of Sussex. It is often claimed that there is no distinct Sussex dialect (Coates, 2010: 29). Even in the earliest works describing the dialect of the area (Wright, 1903) there are suggestions that it cannot be distinguished from Hampshire in the west and Kent in the east.